Variations of the nutritional composition of jujube fruit (Ziziphus jujuba Mill.) during maturation stages. Issue 1 (1st January 2020) - Zhang, Qiong; Wang, Lili; Wang, Zhongtang; Liu, Zhiguo; Zhao, Zhihui; Zhou, Guangfang; Liu, Mengjun; Liu, Ping
ABSTRACT: Identifying the appropriate harvesting stage of jujube fruit is of high interest since the changes in physiological indicators during the fruit maturation may influence the fruit nutritional quality. The present study aimed at assessing the effect of the maturation stages on the nutritional composition and quality of the Chinese jujube variety 'Dongzao.' Fresh fruits were harvested at three consecutive maturity stages: white (W), semi-red (SR), and full-red (R) stage, for analyzing a wide range of nutritional constituents. Our results showed significant effects of the maturity stage on the fruit nutritional constituents. Soluble sugars and dietary fibers (mainly lignin and hemicellulose) highly increased in the fruit. Total flavonoids, carotenoids, and saponin contributing to the antioxidant capacity of the fruit were fairly decreased over the maturity stages. Except for citric, ascorbic, and succinic acids, all the organic acids increased in the fruit. Interestingly, jujube fruit is a good source of essential amino acids (26% of the total amino acids), and also gradually accumulated cyclic nucleotides (cAMP and cGMP) during the maturation. From our results, the semi-red stage seems to be the most appropriate for harvesting the jujube fruit in order to preserve its bioactive compounds.